Transforming Learning: The Role of School-Related Factors in Student Achievement - Abigail Oluyemisi Fadere; Olaolu Paul Akinnubi; Clement Aliu Ogbaini (Nurul Jadid University, 2024)
This study focuses on exploring school-related factors that affect students' academic performance in public high schools in Kwara State, Nigeria. The main objective of this study is to identify and analyze how classroom management, teacher personality, physical environment, and teacher-student ratio contribute to student learning outcomes. This study uses a quantitative approach with a type of correlational descriptive research. Data was collected through structured questionnaire surveys filled out by teachers and students and in-depth interviews with several principals. Data analysis used descriptive and inferential statistics, including Pearson correlation analysis and multiple regression. The results of the study show that classroom management and teacher-student ratio have a significant influence on students' academic performance. Teachers' personalities were also found to have a positive impact, although not as much as the other two factors. Meanwhile, while important, the physical environment has a relatively minor influence on learning outcomes. These findings suggest that the interaction between these factors overall affects students' academic achievement. The implications of this study emphasize the importance of paying more attention to effective classroom management and determining the optimal teacher-student ratio to improve students' academic performance. In addition, the results of this study can be used as a basis for policymakers and education practitioners to design more effective strategies to improve the quality of education in Nigeria. This research also opens up opportunities for more comprehensive follow-up research in understanding the complexity of factors affecting academic performance in various educational contexts.